2015
DOI: 10.1073/pnas.1424683112
|View full text |Cite
|
Sign up to set email alerts
|

Two-level inhibition of galK expression by Spot 42: Degradation of mRNA mK2 and enhanced transcription termination before the galK gene

Abstract: The Escherichia coli gal operon has the structure Pgal-galE-galTgalK-galM. During early log growth, a gradient in gene expression, named type 2 polarity, is established, as follows: galE > galT > galK > galM. However, during late-log growth, type 1 polarity is established in which galK is greater than galT, as follows: galE > galK > galT > galM. We found that type 2 polarity occurs as a result of the downregulation of galK, which is caused by two different molecular mechanisms: Spot 42-mediated degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 32 publications
4
50
0
Order By: Relevance
“…In E. coli, the 109 nt long Spot 42 sRNA encoded by the spf gene is known to downregulate expression of galK, the third gene of the galactose operon galETKM, thereby inhibiting GalK production (Møller et al, 2002). Recent studies suggested that Spot 42 regulates galK expression at two levels: RNA degradation and enhancement of Rho-dependent transcription termination at the galT-galK junction (Wang et al, 2015b). To explain how Rho assures termination at the end of the galT gene, Wang et al (2015b) proposed that the binding site of Spot 42 on the galT-galK junction RNA overlaps with a putative rut site.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…In E. coli, the 109 nt long Spot 42 sRNA encoded by the spf gene is known to downregulate expression of galK, the third gene of the galactose operon galETKM, thereby inhibiting GalK production (Møller et al, 2002). Recent studies suggested that Spot 42 regulates galK expression at two levels: RNA degradation and enhancement of Rho-dependent transcription termination at the galT-galK junction (Wang et al, 2015b). To explain how Rho assures termination at the end of the galT gene, Wang et al (2015b) proposed that the binding site of Spot 42 on the galT-galK junction RNA overlaps with a putative rut site.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%
“…Recent studies suggested that Spot 42 regulates galK expression at two levels: RNA degradation and enhancement of Rho-dependent transcription termination at the galT-galK junction (Wang et al, 2015b). To explain how Rho assures termination at the end of the galT gene, Wang et al (2015b) proposed that the binding site of Spot 42 on the galT-galK junction RNA overlaps with a putative rut site. Spot 42 binding enhances the disassembly of the ribosome at the stop codon of galT and exposes the rut site.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Spot 42 also alters target mRNA levels (75). In-depth study of the galETKM operon revealed that Spot 42 stimulates Rho-dependent transcription termination at the galT-galK junction re-capitulating observations for ChiX (56,81). A non-canonical mechanism of Spot 42 action was observed for the sdhCDAB mRNA encoding succinate dehydrogenase (82).…”
Section: ) (74) Subsequent Work Revealed Thatmentioning
confidence: 99%
“…Recently, Wang et al showed that Spot 42 represses expression of galK through direct binding to the 5 end of the galK mRNA , and also mediates transcription termination of galT in the galT-galK junction. 13 Beisel and Storz demonstrated with microarray analysis and reporter fusions that Spot 42 plays a broader role in metabolism by regulating at least 14 operons. 14 These operons contain a number of genes involved in uptake and catabolism of non-favored carbon sources.…”
Section: Introductionmentioning
confidence: 99%